Estudo Fitoquímico de Piptadenia stipulacea (Fabaceae: Minosoideae) - Sousa, Jéssica Celestino Ferreira (2012)
The genus Piptadenia Benth. part of the Mimosoideae subfamily which is included to the Fabaceae family, the third largest family of angiosperms, widely distributed, being one of the largest in dicotyledonous and economic importance. Piptadenia stipulacea is widely distributed in the caatinga biome, and is used in popular medicine to treat inflammation, activity that has been proven pharmacologically. This paper aims to continue the chemical knowledge of P. stipulacea. The chemical compounds were identified using analysis of data obtained by spectroscopic methods, such as 1H and 13C NMR uni- and bidimensional. The phytochemical study of chloroform phase resulted in the isolation of two flavonoids: 3,3',5,7-tetrahydroxy-4 ,6-dimethoxyflavone and 4 ,5,7- trihydroxy-3 ,6-dimethoxyflavone, both previously described in the species, of ethyl acetate phase resulted in the isolation of a mixture of two novel flavonoids in the species (5,7,4 -trihydroxy-6-methoxyflavone e 3,5,7,4 -tetrahydroxyflavonol), whereas the remaining hydroalcoholic phase resulted in the isolation of an indolic alkaloid: methyl(2-{3-[2-(methylamino)ethyl]-1H-indol-1-yl}ethyl)amine, firstly described in the literature.